Solar energy in the minerals processing industry: identifying the first opportunities - Chiloane, Lehlogonolo Dawn (Centre for Bioprocess Engineering Research, 2015)
Solar energy, particularly electricity generated from the solar resource, has long been thought to be amongst the most expensive energy products. However, in a climate of electricity shortages and pressures on industries to reduce energy-related greenhouse gas emissions, many previous truths are being challenged. In the solar energy field there have emerged several technical and market innovations, thus making it more attractive. This could be of interest to many mining operations which are located in desert-type environments with high solar insolation and far from electricity grids. The objective of this dissertation is to evaluate the use of the available solar energy technologies at utility scale to supply the high energy demand of selected minerals processing industries by co-locating a solar power plant with a minerals processing operation. The effect on how the use of a utility scale solar energy use affects fuel transportation energy and conversion and transmission line losses is assessed. The study analyses the energy usage of different typical minerals processing operations, to identify the processing areas that are likely to benefit from the use of solar energy. Comminution, hot leaching processes and electrowinning circuits are shown to be the most energy intensive areas. Comminution requires high voltage AC power which can be supplied by the solar thermal (ST) technology which converts solar heat to steam which then drives a turbine. Process steam generation can also be achieved directly from ST technology. Electrowinning on the other hand requires low voltage DC electrical output, which can be generated directly using Photovoltaic (PV) technology. Five minerals processing operations, chosen to represent a range of different types of processes and energy supply scenarios, are profiled and their energy requirements quantified as a basis for establishing the extent to which solar energy can augment energy supply in different cases in this industry.